Isolation, characterization and comparative analysis of multi-drug resistant acinetobacter baumannii & vibrio cholerae from hospital wastewater and its adjacent community supply water in Dhaka north - Hasan, Sakib; Labonno, Afia Fahamida; Haque, Mahir Ashhab (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.